Evaluating the Accuracy of Equivalent Static vs. Response Spectrum Method for Seismic Analysis of Buildings of Varying Heights - Shrestha, Rojseen; Shrivastav, Mantu; Pal, Raju (International Journal on Engineering Technology, 2025)
A key choice should be made between Equivalent Static Method (ESM) and Response Spectrum Method (RSM) during the seismic design of buildings. The current paper tests and compares the performance of these two procedures to reinforced concrete dual-system structures of different heights. The cases of 4-story, 8-story, and 16-story regular buildings were modelled with the use of software ETABS v21.0.0 in accordance with the Nepal National Building Code (NBC 105:2020). The important parameters in seismic response comparison such as base shear, roof displacement and maximum inter-story drift were compared. The findings show that an important trend exists, which is, the deviation between the methods grows as the height of the building increases. For base shear, ESM for the 4-story building predicted values 9.9 % and 12.5 % higher in X and Y-direction respectively. However, for the 8-story and 16-story buildings, ESM was found to underestimate the seismic load by approximately 25.1% and 25.4% in the X-direction, and by 24.7% and 25.6% in the Y-direction, respectively, when compared to RSM. Regarding roof displacement in the X-direction, RSM consistently predicted larger values, with the absolute difference growing from 1.39 mm to 14 mm and finally to 31 mm in the 4,8 and 16 story buildings respectively. Similarly, for maximum story drift the absolute difference widened from 0.0191 % to 0.0779 % and finally to 0.1106 % in the 4,8 and 16 story buildings respectively. The paper concludes that the ESM might prove to be adequate in the case of low-rise buildings but cannot be effective in the design of midrise to high rise buildings where the Response Spectrum Method is preferred.